The Second Transition : Eastern Europe in Perspective - Leigh, Daniel (IMF Working Papers; Working Paper, 2009)
The countries of Eastern Europe achieved two remarkable transitions in the short period of the last two decades: from plan to market and, then, in the run-up to and entry into the European Union, they rode a wave of global trade and financial market integration. Focusing on the second transition, this paper reaches three conclusions. First, by several metrics, East European and East Asian growth performances were about on par from the mid-1990s; both regions far surpassed Latin American growth. Second, the mechanisms of growth in East Europe and East Asia were, however, very different. East Europe relied on a distinctive-often discredited-model, embracing financial integration with structural change to compensate for appreciating real exchange rates. In contrast, East Asia contained further financial integration and maintained steady or depreciating real exchange rates. Third, the ongoing financial turbulence has, thus far, not had an obviously differential impact on emerging market regions: rather, the hot spots in each region reflect individual country vulnerabilities. If the East European growth model is distinctive, is it sustainable and replicable? The paper speculates on the possibilities.